2018
DOI: 10.3390/ijms19113637
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Classification, and Functional Analysis of AP2/ERF Family Genes in the Desert Moss Bryum argenteum

Abstract: Bryum argenteum is a desert moss which shows tolerance to the desert environment and is emerging as a good plant material for identification of stress-related genes. AP2/ERF transcription factor family plays important roles in plant responses to biotic and abiotic stresses. AP2/ERF genes have been identified and extensively studied in many plants, while they are rarely studied in moss. In the present study, we identified 83 AP2/ERF genes based on the comprehensive dehydrationrehydration transcriptomic atlas of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 46 publications
4
18
0
Order By: Relevance
“…AP2/ERFs in Arabidopsis are classified via two different systems 3 , 4 , and both classification systems have been used to classify the AP2/ERF family proteins in other plant species, including celery and buckwheat 26 , 27 . Advancements in sequencing technology and the availability of large datasets have aided the identification of AP2 / ERF family genes in several plant species by the use of genomic, transcriptomic or EST data 28 , 29 . Current data on the molecular and genetic properties of Pinaceae species are lacking due to the large genome sizes of Pinaceae species, the sizes of which are nearly 20 Gb 30 , and access to the genomic information is limited.…”
Section: Discussionmentioning
confidence: 99%
“…AP2/ERFs in Arabidopsis are classified via two different systems 3 , 4 , and both classification systems have been used to classify the AP2/ERF family proteins in other plant species, including celery and buckwheat 26 , 27 . Advancements in sequencing technology and the availability of large datasets have aided the identification of AP2 / ERF family genes in several plant species by the use of genomic, transcriptomic or EST data 28 , 29 . Current data on the molecular and genetic properties of Pinaceae species are lacking due to the large genome sizes of Pinaceae species, the sizes of which are nearly 20 Gb 30 , and access to the genomic information is limited.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a total of 142 non-redundant ERF genes were identified from the Capsicum annuum genome. The ERF family in Arabidopsis (122) [ 15 ], watermelon (120) [ 36 ], rice (143) [ 39 ], Chinese cabbage (248) [ 40 ], cauliflower (146) [ 36 ] and Bryum argenteum (75) [ 41 ] were successfully identified and investigated. These results indicated that the number of ERF genes in different plants was distinct.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a total of 142 non-redundant ERF genes were identi ed from the Capsicum annuum genome. The ERF family in Arabidopsis (122) [15], watermelon (120) [48], rice (143) [51], Chinese cabbage (248) [52], cauli ower (146) [48] and Bryum argenteum (75) [53] were successfully identi ed and investigated. These results indicated that the number of ERF genes in different plants was distinct.…”
Section: Discussionmentioning
confidence: 99%